Interaction induced hybridization of Majorana zero modes in a coupled quantum-dot-superconducting-nanowire hybrid system - Ricco, L. S. [UNESP]; Marques, Y.; Sanches, J. E. [UNESP]; Shelykh, I. A.; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2020)
We study the low-energy transport properties of a hybrid device composed by a native quantum dot coupled to both ends of a topological superconducting nanowire section hosting Majorana zero modes. The account of the coupling between the dot and the farthest Majorana zero mode allows one to introduce the topological quality factor, characterizing the level of topological protection in the system. We demonstrate that the Coulomb interaction between the dot and the topological superconducting section leads to the onset of the additional overlap of the wave functions describing the Majorana zero modes, leading to the formation of trivial Andreev bound states even for spatially well-separated Majoranas. This leads to the spoiling of the quality factor and introduces a constraint for the braiding process required to perform topological quantum computing operations.